Structural mechanisms formative (Goldman) reading done Studio talk And their role in raising Criticism knowledge (Al-Academy, 2017)
Facing the receiver (critic) problematic understanding of modern art done, which turned positive professional image to symbolic language, which gave it authenticity previous Arts advantage, and this latest progress in critical reading contemporary and several mechanisms for analyzing literary texts and plastic, including textural fabric. And we suffer from the absence of cash the recipient culture (learner), so the current search goal focused on detecting structural mechanisms formative (Goldman) reading done modern art and its role in raising criticism knowledge (learner). Defining the theoretical framework of chapter II by discussing it; the first episode dealt with the textural fabric, while the latter was accomplished Studio talk, and the third dealing with education, knowledge, and concluded the season with several indicators. Chapter III research methodology were presented in terms of analytical, descriptive and analysis mechanism described as textural fabric structures, Goldman four (Interior, cultural, social, and historical) in the form of educational applications in reading samples elected performed modern plastic. And produced results that knowledge of mental activity cash depends on experience and training to receive technical product, as well as formative symbolic system modularization defines the modern plastic each completed its cultural, social and historical. Based on the above, the researcher recommended hiring art criticism contemporary art concepts development of postmodernism to art education students